Kantor Sewa Di Pekanbaru Dengan Pendekatan Arsitektur Hijau - Epriga, M Arseli; Susilawati, Mira Dharma; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru is the capital of Riau province which became one of the provinces whose economic growth is very rapid. From a small economic sector even to business and foreigninvestors are in Pekanbaru. Pekanbaru also has become a destination town of investors both from within the country and also abroad have been widely developed in Pekanbaru. However the facilities and space requirements to support the economy so is slightly. Therefore, the rental office is becoming one of the alternatives for developing the economic sector in Pekanbaru. In the design of the rental office, applied design approach emphasizes the principles of green architecture withthe aim of building that is designed into the building to minimize bad influence on the environment, nature, and human and produce a better and more healthy. However, to support this design is also applied in the concept of